Precise implications for real‐space pair distribution function modeling of effects intrinsic to modern time‐of‐flight neutron diffractometers. Issue 4 (6th June 2018) - Olds, Daniel; Saunders, Claire N.; Peters, Megan; Proffen, Thomas; Neuefeind, Joerg; Page, Katharine
Abstract : A systematic overview of the effects of common aberrations in time‐of‐flight neutron powder diffraction data on real‐space pair distribution functions is provided, and methods and best practices to mitigate these effects are discussed. Abstract : Total scattering and pair distribution function (PDF) methods allow for detailed study of local atomic order and disorder, including materials for which Rietveld refinements are not traditionally possible (amorphous materials, liquids, glasses and nanoparticles). With the advent of modern neutron time‐of‐flight (TOF) instrumentation, total scattering studies are capable of producing PDFs with ranges upwards of 100–200 Å, covering the correlation length scales of interest for many materials under study. Despite this, the refinement and subsequent analysis of data are often limited by confounding factors that are not rigorously accounted for in conventional analysis programs. While many of these artifacts are known and recognized by experts in the field, their effects and any associated mitigation strategies largely exist as passed‐down `tribal' knowledge in the community, and have not been concisely demonstrated and compared in a unified presentation. This article aims to explicitly demonstrate, through reviews of previous literature, simulated analysis and real‐world case studies, the effects of resolution, binning, bounds, peak shape, peak asymmetry, inconsistent conversion of TOF to d spacing and merging of multiple banks in neutron TOF data as they directly relate to real‐space PDF analysis. Suggestions for best practice in analysis of data from modern neutron TOF total scattering instruments when using conventional analysis programs are made, as well as recommendations for improved analysis methods and future instrument design.